Mortality in Individuals with Subjective Cognitive Decline: Results of the Leipzig Longitudinal Study of the Aged (LEILA75+). - Luck, T.; Roehr, S.; Jessen, F.; Villringer, A.; Angermeyer, M. C.; Riedel-Heller, S. G. (J Alzheimers Dis, 2015)
BACKGROUND: Studies have shown that dementia and cognitive impairment can increase mortality, but less is known about the association between subjectively perceived cognitive deficits (subjective cognitive decline, SCD) and mortality risk. OBJECTIVE: In this study, we analyzed mortality in non-demented individuals with SCD in a general population sample aged 75+ years. METHOD: Data were derived from the Leipzig Longitudinal Study of the Aged (LEILA75+). We used the Kaplan-Meier survival method to estimate survival times of individuals with and without SCD and multivariable Cox proportional hazards regression to assess the association between SCD and mortality risk, controlled for covariates. RESULTS: Out of 953 non-demented individuals at baseline, 117 (12.3% ) expressed SCD. Participants with SCD showed a significantly higher case-fatality rate per 1,000 person-years (114.8, 95% CI = 90.5-145.7 versus 71.7, 95% CI = 64.6-79.5) and a significantly shorter mean survival time than those without (5.4 versus 6.9 years, p < 0.001). The association between SCD and mortality remained significant in the Cox analysis; SCD increased mortality risk by about 50% (adjusted Hazard Ratio = 1.51) during the study period. Besides SCD, older age, male gender, diabetes mellitus, stroke, and lower global cognitive functioning were also significantly associated with increased mortality. CONCLUSION: Our findings suggest an increased mortality risk in non-demented older individuals with SCD. Even though further studies are required to analyze potential underlying mechanisms, subjective reports on cognitive deficits may be taken seriously in clinical practice not only for an increased risk of developing dementia and AD but also for a broader range of possible adverse health outcomes.
Keywords: Aged; Aged, 80 and over; *Aging; Cognition Disorders/epidemiology/*mortality/*psychology; Community Health Planning; Female; Germany; Humans; Kaplan-Meier Estimate; Longitudinal Studies; Male; Neuropsychological Tests; Psychiatric Status Rating Scales